Thermocatalytic Hydrolysis of Tri-6-bromo-2,4-dichlorophenyl Phosphate by kinetic Methods - Gupta, H.M.; Prabha, S. (Asian Journal of Chemistry, 2012)
The hydrolysis of tri-6-bromo-2,4-dichlorophenyl orthophosphate by kinetic studies is reported here in the acid range (0.01-4.5 M HCl) in 50% aqueous dioxane at 90 ºC to highlight some characteristic features like: (i) involvement of only one reactive form, the conjugate acid species, in the entire acid range examined, as shown by neutral electrolyte effect data and also by concordance between the observed and the calculated rates, (II) demonstration of an ill defined maximum at the normal value of 4 M, (iii) higher rates due to solvation by dioxane in spite of decrease in <span style="font-family: Symbol; font-size: 12pt; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">e with rise in percentage of dioxane in the mixed solvent, (iv) indirect hydrolysis via the formation of the corresponding diester, as derived by mirror method calculation, and (v) effect of mixed-halogen substitutents (both electronic as well as steric) in over-simplication of its hydrolysis, the overall hydrolysis is bimolecular and proceeds with P-O- bond fission.